2000
DOI: 10.1023/a:1006402614838
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Despite multimodal therapy, glioblastoma multiforme (GBM) is associated with a poor prognosis with a median survival of less than 1 year. However, a small number of patients with GBM shows survival times of several years. Although clinical features like age and performance status at diagnosis are well known prognostic parameters, molecular markers for prognosis of overall survival are still lacking. Therefore, we compared 2 age- and gender-matched groups of GBM patients with different post-operative time to tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Although multiple clinical studies have suggested that PTEN mutation in glioma has no correlation with survival or chemosensitivity [7], [8], [9], [10], some other studies have associated loss of function of PTEN with a more adverse outcome [11], [12], [13]. Unfortunately, many of these studies lack the sample size or thorough evaluation of PTEN genetic alterations to make concrete conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple clinical studies have suggested that PTEN mutation in glioma has no correlation with survival or chemosensitivity [7], [8], [9], [10], some other studies have associated loss of function of PTEN with a more adverse outcome [11], [12], [13]. Unfortunately, many of these studies lack the sample size or thorough evaluation of PTEN genetic alterations to make concrete conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most common and aggressive human brain cancer, accounting for about 15% of all intracranial tumors [1][3]. Despite advances in chemotherapy, surgical and radiation oncology, the prognosis of this tumor remains very poor [4][6].…”
Section: Introductionmentioning
confidence: 99%
“…PTEN activity converts PIP3 to PIP2, thus regulating the level of activation of these downstream pathways. Constitutive activation of the Akt and/or mTOR pathways and loss of function of PTEN can each contribute to tumor progression [27, 28]. …”
Section: Introductionmentioning
confidence: 99%